A comparative study on the properties of potentially bioactive glasses obtained by sol-gel technique and by melting mixtures of oxides - Avrami, Daniela (2017)
Phosphocalcic glasses, based on ternary system SiO2 - CaO- P2O5 and those doped with copper (SiO2 ? CaO - P2O5 -Cu2O) can be obtained by the traditional method of sub-cooling melts or modern methods such as process that uses mechanical energy, neutrons action, deposition in thin layers or by sol-gel technique. This paper shows the experimental results of threecompositional phosphocalcic glasses: 50% SiO2 - 43% CaO - 7% P2O5 , 50% SiO2 - 38% CaO - 7% P2O5 - 5% Cu2O obtained through sol-gel method and 45% SiO2 - 22.5% CaO - 22.5 Na2O - 5% P2O5 - 5% Cu2O obtained by melting. In order to study their bioactivity, the three compositions were structural analyzed by X-ray diffraction method. In this case the apatite formation washighlighted after soaked in simulated body fluid, but also other compounds (CaCO3 and CuO) resulting from the same process were observed. In case of the melting glass apatite formation has not been highlighted. The functional groups present in the structure of glasses before and after soaking (PO43-, CO32- and HO-) were highlighted by the Fourier Transform Infrared Spectroscopy (FTIR). The elemental chemical composition was confirmed by elemental analysis WD-XRF. The morphology of sol-gel glass powders was revealed by SEM analysis. All glass compositions were tested in terms of antibacterial activity in vitro.